The suicide tourist [videorecording (DVD)] - Zaritsky, John; Zaritsky, John (PBS Distribution, 2010)
Do we have the right to end our lives if life itself becomes unbearable, or we are terminally ill? With unique access to Dignitas, the Swiss non-profit that has helped over one thousand people die, filmmaker John Zaritsky offers a revealing look at two couples facing the most difficult decision of their lives, and lets us see as one Chicago native makes the trip to Switzerland for what will become the last day of his life.